Pengaruh Audit Tenure, Rotasi Kap, Dan Ukuran Kap Terhadap Kualitas Audit - Farhan Khairullah; Ivan Yudianto (GLOBAL SCIENTS PUBLISHER, 2025)
As an entity managed by the government, State-Owned Enterprises (SOEs) companies have a great responsibility to present financial reports that are reliable, fair and in accordance with actual conditions, so that they meet the needs of stakeholders. The quality of good financial statements is in line with the quality of the audit carried out. This study aims to analyse the effect of audit tenure, KAP rotation, and KAP size on audit quality. This study uses secondary data from annual reports and financial reports of 20 state-owned companies listed on the Indonesia Stock Exchange during the 2019-2023 period. The independent variables include audit tenure, KAP rotation, and KAP size, while audit quality is the dependent variable. The sample was selected using purposive sampling method, and the analysis was conducted using multiple linear regression with SPSS software at 5% significance level. The results showed that audit tenure has no significant effect on audit quality, while KAP rotation and KAP size have a significant effect on audit quality.